Porous titanium microsphere kyphoplasty for augmentation treatment of osteoporotic vertebral fractures: Technical report and case series - Tartara, Fulvio; Armocida, Daniele; Garbossa, Diego; Meli, Francesco; Costantino, Gabriele; Cofano, Fabio; Francaviglia, Natale (Frontiers in Surgery, 2023)
Background Vertebral augmentation procedures (VAPs) are used in cases of persistent and unresponsive pain in patients with vertebral compression fractures (VCFs). Although VAPs are considered a safe procedure providing quick pain relief and improved physical function, some postoperative complications can occur, for example, bone cement leakage. The material used in this procedure is almost exclusively polymethyl methacrylate (PMMA), which appears to lack biological activity and osteointegration capabilities. In this study, we introduce a new filling system consisting of cannulas preloaded with titanium microspheres, which stabilizes and consolidates the structure of the vertebral body in treating VCFs after the performance of the kyphoplasty procedure. Methods We report a retrospective case series of six patients affected by osteoporotic vertebral fractures with worsening back pain, neurologic impairment, and failed conservative treatment who underwent the VAP at our institute, for which the SPHEROPLAST [MT ORTHO s.r.l., Aci Sant’Antonio (CT), Italy] system was used. Results The patients had failed an average conservative trial of 3.9 weeks before they presented to us with neurodeficit. There were two men and four women with a mean age of 74.5 years. The average hospital stay was 2 days. There were no reported perioperative complications related to cement injection, such as intraoperative hypoxia, hypotension, pulmonary embolization, myocardial infarction, neurovascular or viscera injury, or death. The VAS score significantly decreased from a mean preoperative of 7.5 (range 6–19) to 3.8 (range 3–5) immediately after surgery and 1.8 (range 1–3). Conclusion We report the first clinical results in a series of six patients treated for VCF using the microsphere system after analyzing the clinical results produced by, and the complications that arose from, this new device. In patients with VCF, the VAP using titanium microspheres appears to be a feasible and safe procedure with a low risk of material leakage.